Anyuan : Mining China's Revolutionary Tradition - Perry, Elizabeth J. (Book collections on Project MUSE., 2012)
How do we explain the surprising trajectory of the Chinese Communist revolution? Why has it taken such a different route from its Russian prototype? An answer, Elizabeth Perry suggests, lies in the Chinese Communists' creative development and deployment of cultural resources - during their revolutionary rise to power and afterwards. Skillful "cultural positioning" and "cultural patronage," on the part of Mao Zedong, his comrades and successors, helped to construct a polity in which a once alien Communist system came to be accepted as familiarly "Chinese." Perry traces this process through.